2016
DOI: 10.1891/0886-6708.vv-d-14-00047
|View full text |Cite
|
Sign up to set email alerts
|

“Yeah, We Serve Alcohol, but . . . We Are Here to Help”: A Qualitative Analysis of Bar Staff’s Perceptions of Sexual Violence

Abstract: This study is an exploratory analysis of how bar staff perceive their role in preventing sexual harassment and assault. In particular, through qualitative focus group interviews, this study explores bar staff's attitudes surrounding sexual harassment/assault, how they currently handle these situations, and their opinions regarding programs and policies that currently mandate responsibility. Six major themes emerged including their hesitation to discuss sexual violence, their unique position as a service provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 24 publications
2
30
0
2
Order By: Relevance
“…Education surrounding capacity to make decisions and drug-taking would likely reduce victim-blaming attitudes (e.g., that women put themselves at risk of sexual violence when they consume substances) amongst jurors. Powers and Leili (2016) found that a lack of knowledge and education surrounding sexual consent and alcohol intoxication has prevented individuals who work in the bar industry from feeling able to intervene in sexual harassment scenarios (i.e., because they did not know what legally constituted being "too drunk" to have sex). Therefore, information on capacity to make sexual decisions in the context of drug-taking would likely be beneficial to future education initiatives, such as bystander prevention programmes, targeting bar/club staff, sex-on-premises venue staff, or Chemsex party organizers/attendees.…”
Section: Capacity To Make Sexual Decisionsmentioning
confidence: 99%
“…Education surrounding capacity to make decisions and drug-taking would likely reduce victim-blaming attitudes (e.g., that women put themselves at risk of sexual violence when they consume substances) amongst jurors. Powers and Leili (2016) found that a lack of knowledge and education surrounding sexual consent and alcohol intoxication has prevented individuals who work in the bar industry from feeling able to intervene in sexual harassment scenarios (i.e., because they did not know what legally constituted being "too drunk" to have sex). Therefore, information on capacity to make sexual decisions in the context of drug-taking would likely be beneficial to future education initiatives, such as bystander prevention programmes, targeting bar/club staff, sex-on-premises venue staff, or Chemsex party organizers/attendees.…”
Section: Capacity To Make Sexual Decisionsmentioning
confidence: 99%
“…For many bartenders, peak hours constitute something of a sensory overdrive with sustained exposure to loud music, noise, heat, light shows and orders from all sides (Powers & Leili, 2016). In the long run, such sensory overdrive can be exhausting and take its toll on health (Tutenges, Bøgkjaer, Witte, & Hesse, 2013), and it can also thwart rational thinking, lower conflict resolution skills, and amplify the difficulties of assessing the age and level of intoxication of patrons (Hughes et al, 2012).…”
Section: Workplace Environment and Coping Strategiesmentioning
confidence: 99%
“…Several studies indicate that refusing to serve a customer can easily lead to conflict, which is what bartenders wish to avoid (Leo, 2013;McKnight, 1991;Stockwell, 1992). In addition, bartenders are naturally concerned with getting tips and, therefore, the use of server interventions is not appealing because that can directly influence their earnings (Powers & Leili, 2016). Moreover, serving staff lack significant incentives to serve alcohol responsibly, not least because of the dearth of enforcement targeting overserving (Lenk, Toomey, Nelson, Jones-Webb, & Erickson, 2014;Toomey et al, 2016).…”
Section: Workplace Environment and Coping Strategiesmentioning
confidence: 99%
“…En hovedvekt av bartenderstudier er kvantitative og fokuserer på problemorienterte forhold ( Buvik & Tutenges, 2017 ). Studiene fokuserer i hovedsak på negative forhold som overskjenking ( Buvik, 2013 ; Buvik & Rossow, 2015 ; Goodsite, Klear, & Rosenberg, 2008 ; Leo, 2013 ; Reiling & Nusbaumer, 2006 ), seksuelle overgrep og trakassering ( Bråten & Øistad, 2017 ; Graham et al, 2014 ; Powers & Leili, 2016 ), bartenderes høye alkoholkonsum og illegale rusbruk ( Buvik, Bye, & Gripenberg, 2018 ; Kjaerheim & Mykletun, 1995 ; Larsen, 1994 ; Norström, Sundin, Müller, & Leifman, 2012 ) eller bartenderes rolle på utesteder med mye vold ( Graham & Homel, 2008 ; Hobbs, Hadfield, Lister, & Winlow, 2002 ). Flere norske studier legger vekt på bartenderes manglende arbeidsrettigheter og krevende arbeidsforhold ( Bråten & Sletvold Øistad, 2017 ; Trygstad et al, 2014 ).…”
unclassified
“…Blant annet har muligheten til å forhindre alkoholmisbruk og bartenderes rolle som samtaleterapeut for alkoholmisbrukere blitt studert ( Bissonette, 1977 ; Waring & Sperr, 1982 ). Det samme har muligheten til å intervenere mot seksuell vold på utesteder ( Powers & Leili, 2016 ). Ocejo (2010 , 2012 ) viser gjennom studier av bartendere i et populært utelivsområde i New York hvordan en spesiell undergruppe av bartendere, cocktailbartendere, synes å inneha en egen status innen utelivet, og således skiller seg fra andre typer bartendere og serviceyrker.…”
unclassified